ANALISIS HUKUM SYARIAH TERHADAP PRAKTIK GADAI EMAS DI PEGADAIAN CABANG BATUNYALA, KECAMATAN PRAYA TENGAH - Jayadi, Usman; Sabeni, Ahmad; Salihin, Agus (CV. Lafadz Jaya, 2023)
The practice of pawning gold has become the community's main choice in meeting urgent financial needs. This article analyzes the practice of gold pawning at Pegadaian Batunyala Branch, Central Praya District from the perspective of sharia economic law. This research uses a qualitative method with a descriptive analytical approach. The research results show that the practice of gold pawning at Pegadaian Batunyala Branch is largely in accordance with sharia principles, but there are still several aspects that need to be improved. It is hoped that these findings can contribute to the development of a fairer and more efficient sharia pawning system.